2010
DOI: 10.1007/s11199-010-9840-0
|View full text |Cite
|
Sign up to set email alerts
|

The Division of Household Labor in Spanish Dual Earner Couples: Testing Three Theories

Abstract: Although the participation of men in household activities has increased, this has not prompted an equitable division of household activities among men and women, since Spanish women continue to perform a greater share of these activities than Spanish men. This article explores the explanatory potential of three theoretical approaches (traditional gender division, role-strain and the resourcebargaining approach) to account for the emergence of different patterns in the division of unpaid work among Spanish dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 50 publications
1
10
0
2
Order By: Relevance
“…However, the mixed findings regarding gender differences in the experience of role conflict (i.e., differences in the experience WIF but not in the experience FIW) are consistent with the results of other studies in the field (Giebels & Janssen, 2004; McElwain, Korabik, & Rosin, 2005) and reflect the changes in gender roles in the contemporary era, which are mainly evident in the area of household tasks (Kulik, 2013). It is possible that because men tend to participate more actively in household tasks today than they did in the past, the interference of family demands with work affects both genders to the same extent (Gaunt & Bouknik, 2012; Goñi-Legaz, Ollo-Lopez, & Bayo-Moriones, 2010), as the findings of the present study revealed.…”
Section: Discussionsupporting
confidence: 46%
“…However, the mixed findings regarding gender differences in the experience of role conflict (i.e., differences in the experience WIF but not in the experience FIW) are consistent with the results of other studies in the field (Giebels & Janssen, 2004; McElwain, Korabik, & Rosin, 2005) and reflect the changes in gender roles in the contemporary era, which are mainly evident in the area of household tasks (Kulik, 2013). It is possible that because men tend to participate more actively in household tasks today than they did in the past, the interference of family demands with work affects both genders to the same extent (Gaunt & Bouknik, 2012; Goñi-Legaz, Ollo-Lopez, & Bayo-Moriones, 2010), as the findings of the present study revealed.…”
Section: Discussionsupporting
confidence: 46%
“…Despite the changes in gender roles in recent decades, research findings indicate that as they did in the past, women still devote significantly more hours than men to household chores and childcare (e.g., Goñi-Legaz, Ollo-López, & Bayo-Moriones, 2010), whereas men devote significantly more hours to the work domain than women (e.g., Stier, 2010). Thus, as in the past, women still show a greater tendency than men to perceive family roles as their main responsibility, whereas men show a greater tendency to perceive the employment role as their main responsibility (Christiansen & Palkovitz, 2001).…”
Section: Role Conflict and Emotional Well-being: Gender Differencesmentioning
confidence: 93%
“…For instance, with the rise in dual-earner heterosexual couples, husbands have nearly doubled their household work and increased their time with children, but wives continue to do the majority of domestic and childcare work in the U.S (Bianchi 2011;Bianchi et al 2012). Research in Spain also finds a slight increase in husbands' household work over time, but that wives are still primarily responsible for the domestic labor (Goni-Legaz et al 2010). Therefore, the perception of women as ideally-motivated may not only serve to limit continued changes for women, but also to limit the possibility of role change for men.…”
Section: Discussionmentioning
confidence: 99%